SURGICAL TREATMENT OUTCOME OF AMNIOTIC BAND SYNDROME (ABS) INVOLVING THE FINGER AND LEG WITH INFECTION OF A FOUR-MONTHS MALE CHILD: A CASE REPORT - Hendra Cahya Kumara; Pamudji Utomo; Umar Kharisma Islami; Adhitya Indra Pradhana (Universitas Muhamadiyah Surakarta, 2020)
ABSTRACTAmniotic band syndrome is an uncommon congenital disorder without any genetic or hereditary predisposition factor. It involves fetal entrapment in strands of amniotic tissue and causes an array of deletions and deformations. The aim of this article was to report surgical treatment outcome of amniotic band syndrome finger and infected intrauterine leg amputation. A case of four months male child with complaint of incomplete formation and constricting band on his left leg was reported. On the stump of left leg initially there was a small lump. Over time the size of the stump grew bigger and infected wound appeared. Other deformities were constricting band on proximal phalanx of the middle finger of left hand, acrosyndactyly of first and second toe of right foot and congenital scrotalis hernia. We performed a release surgery of constriction ring band of proximal phalanx of the middle finger of left hand with z-plasty incision and below knee amputation for left leg. We followed up patient in one year after operation. The patient complained no pain and no sign of infection. Patient could walk normally and independently with good activity daily living. We concluded that procedure with z-plasty incision had good result and avoided morbidity. Below knee amputation procedure and application of suitable prosthesis provided satisfying outcome on patient activity daily living and ambulation. Key words: Amniotic band syndrome, intrauterine amputation, z-plasty, infectioABSTRAKSindrom amniotic band merupakan kelainan bawaan yang jarang terjadi dan tanpa adanya kecenderungan faktor genetik atau keturunan. Kelainan ini diakibatkan terlilitnya janin dalam untaian jaringan amnion dan menyebabkan berbagai jenis kehilangan dan kecacatan. Tujuan dari artikel ini adalah melaporkan luaran tatalaksana operasi sindrom amniotic band pada jari tangan dan amputasi pada tungkai yang terinfeksi intrauterine. Pasien adalah seorang anak laki-laki empat bulan dengan amputasi tungkai bawah kiri disertai constriction band pada bagian proksimal. Pada ujung tungkai bawah kiri didapatkan benjolan dengan ukuran minimal yang makin lama ukuran sisi distal menjadi lebih besar dan tampak luka dengan nanah. Kelainan bentuk lainnya adalah constricting band pada phalanx proksimal jari tengah tangan kiri, acrosyndactyly jari kaki pertama dan kedua kaki kanan serta congenital hernia skrotalis. Kami melakukan operasi release constriction ring band phalanx proximal jari tengah tangan kiri dengan irisan z-plasty dan below knee amputation tungkai kiri. Follow up pasien setelah operasi satu tahun. Tidak ada keluhan nyeri, tidak ada tanda infeksi, pasien dapat berjalan normal dan aktivitas sehari-hari dengan mandiri. Kesimpulan bahwa prosedur dengan irisan z-plasty memberikan hasil yang baik dan menghidari morbiditas pasien. Prosedur below knee amputation dan penggunaan prosthesis yang tepat memberikan hasil yang memuaskan pada aktivitas sehari-hari dan ambulasi pasien. Kata kunci: Sindrome amniotic band, amputasi intrauterine, z-plasty, infeksi